Analisis Kesalahan Penggunaan Bahasa Oleh Netizen Di Media Sosial Tiktok - Muhammad Surip; Ruben Kornelius Sitio; Sarah Elexsa Siahaan; Thiessca Theofani Lumbantoruan (Pragmatik : Jurnal Rumpun Ilmu Bahasa dan Pendidikan, 2024)
Indonesian is the official language of the Indonesian nation which is used by all Indonesian people. The increasingly rapid development of technology can influence society, one of which is the correct use of Indonesian, especially among students who often use slang. This research discusses the bad use of Indonesian language etiquette on social media, especially Tiktok. In this research, researchers used descriptive methods to identify language errors that occur on social media, especially on Tiktok. The aim of this research is to describe the use of toxic language in comments by content creators. The research results show that the use of Indonesian on social media, especially on TikTok, often experiences errors in spelling, diction and grammatical structure. These mistakes can lead to misunderstandings and ineffective use of language. The conclusion of this research shows that the unethical use of Indonesian on social media can have a negative impact on individuals. Therefore, more awareness and attention is needed in using Indonesian on social media in order to communicate effectively and not cause misunderstandings.